Pengaruh Literasi Keuangan dan Gaya Hidup Hedonisme terhadap Perilaku Keuangan pada Mahasiswa - Rahmawati, Nur; Fauziah, Fenty; Jamal, Sri Wahyuni (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to examine the influence of financial literacy and hedonistic lifestyle on the financial behavior of undergraduate management students at Universitas Muhammadiyah Kalimantan Timur. Financial literacy refers to an individual’s ability to understand, believe in, and effectively manage personal finances. Meanwhile, a hedonistic lifestyle reflects a tendency to pursue short-term pleasures without considering long-term financial consequences. This research employed a quantitative approach using a survey method, with data collected through questionnaires distributed to 100 active students. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results indicate that financial literacy has a positive and significant effect on students’ financial behavior. In contrast, a hedonistic lifestyle does not have a significant partial effect; however, when combined with financial literacy, both variables have a significant simultaneous influence. These findings highlight the importance of improving financial literacy to foster healthier financial behavior and help students make wiser decisions when facing consumer lifestyle pressures.